2006
DOI: 10.1203/01.pdr.0000219860.96732.09
|View full text |Cite
|
Sign up to set email alerts
|

Type-I But Not Type-II Interferon Receptor Knockout Mice Are Susceptible to Biliary Atresia

Abstract: ABSTRACT:The etiology of biliary atresia (BA) is not yet understood, but recent studies have shown inflammation with an upregulated interferon (IFN) activity in the intra-and extrahepatic bile ducts of patients with BA. These findings support an inflammatory/ infectious cause of BA as mimicked in our infective murine model. To study the role of the IFN receptors in our model, we used mice with inactivated INF-alpha/beta receptor A129, with inactivated IFNgamma receptor G129, or inactivation of both interferon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 26 publications
2
9
0
1
Order By: Relevance
“…These findings support the conclusion that the STAT1-dependent IFN signaling responses are critical for controlling systemic replication of the heterologous simian RRV strain. In addition, these findings confirmed previous reports that IFN-␣/␤ is more important than IFN-␥ in clearing RRV systemic infection (36). However, in the present study type I and II IFNs appeared to be functioning collaboratively in restricting systemic replication and disease, since knockout of either the IFN-␣/␤ or IFN-␥ receptor alone did not result in the full-blown lethal disease syndrome.…”
Section: Fig 8 Detection Of Rrv-infected Inflammatory Cells In Extrsupporting
confidence: 92%
“…These findings support the conclusion that the STAT1-dependent IFN signaling responses are critical for controlling systemic replication of the heterologous simian RRV strain. In addition, these findings confirmed previous reports that IFN-␣/␤ is more important than IFN-␥ in clearing RRV systemic infection (36). However, in the present study type I and II IFNs appeared to be functioning collaboratively in restricting systemic replication and disease, since knockout of either the IFN-␣/␤ or IFN-␥ receptor alone did not result in the full-blown lethal disease syndrome.…”
Section: Fig 8 Detection Of Rrv-infected Inflammatory Cells In Extrsupporting
confidence: 92%
“…Interferons seem to play a crucial role in this model, as Mx protein (an IFN type I specific indicator) persists in hepatocytes, bile ducts and intrahepatic endothelial cells of cholestatic mice beyond the second week after RRV infection [107,108]. In other studies, for instance with IFN-receptor knock-out mice, it can be shown that IFN type II attenuates the tropism of lymphocytes to bile ducts and is somehow imperative to the development of BA [99,109].…”
Section: Introductionmentioning
confidence: 99%
“…Without a functional interferon system, AG129 mice support both the spread from the primary infection site and the persistence in vivo of a number of viruses, including dengue virus (29), Sindbis virus (24), and rhesus rotavirus (10). IFNs have also been shown to play an important role in the antiviral defense against EV71 infection.…”
mentioning
confidence: 99%